2012
DOI: 10.1002/path.4043
|View full text |Cite
|
Sign up to set email alerts
|

Cellular ageing, increased mortality and FTLD‐TDP‐associated neuropathology in progranulin knockout mice

Abstract: Loss-of-function mutations in progranulin (GRN) are associated with frontotemporal lobar degeneration with intraneuronal ubiquitinated protein accumulations composed primarily of hyperphosphorylated TDP-43 (FTLD-TDP). The mechanism by which GRN deficiency causes TDP-43 pathology or neurodegeneration remains elusive. To explore the role of GRN in vivo, we established Grn knockout mice using a targeted genomic recombination approach and Cre-LoxP technology. Constitutive Grn homozygous knockout (Grn(-/-) ) mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
119
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 42 publications
14
119
2
Order By: Relevance
“…PGRN deficiency resulted in neuronal loss, increased gliosis, lipofuscin accumulation in the VPM/VPL, and defective myelination in the cerebral cortex. These pathological changes in aged PGRN-deficient mice are partially consistent with previous studies [11,13,33], though the brain regions examined were different. Analyses using NCL model mice in the previous studies revealed that glial activation precedes neuronal loss in the VPM/VPL [17,34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PGRN deficiency resulted in neuronal loss, increased gliosis, lipofuscin accumulation in the VPM/VPL, and defective myelination in the cerebral cortex. These pathological changes in aged PGRN-deficient mice are partially consistent with previous studies [11,13,33], though the brain regions examined were different. Analyses using NCL model mice in the previous studies revealed that glial activation precedes neuronal loss in the VPM/VPL [17,34].…”
Section: Discussionsupporting
confidence: 91%
“…Disruption of both the ubiquitin-proteasome system and the autophagy-lysosomal system is one of the characteristic features of FTLD with TDP-43 inclusions in the cytoplasm of neurons [27], and impaired production of PGRN is involved in this pathology [5][6][7]. Previous studies reported increased TDP-43 phosphorylation in PGRN-deficient mice [11,13,28]. In the present study, TDP-43 colocalized with p62 in the cytoplasm of neurons as well as the phosphorylated TDP-43 aggregate in the VPM/VPL were only observed in aged PGRN-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al (7) recently showed that intracytoplasmic ubiquitinated aggregates observed in these mice are probably composed of lipofuscin. This finding was replicated in an independent Grn Ϫ/Ϫ line (36). Although some vacuolation was observed in the habenula and hippocampus in very old (23 months) Grn Ϫ/Ϫ mice (7), overt neuronal loss seems to be very mild or absent (34), in contrast with the severe atrophy observed in human FTLD.…”
Section: Mouse Models Of Progranulin Deficiencymentioning
confidence: 74%
“…Behaviorally, the most consistent finding is social interaction deficits (33)(34)(35). In a classic test of hippocampal learning and memory (Morris water maze), Grn Ϫ/Ϫ mice had mild deficits at old age (18 -21 months) in two studies (33,36) but no deficits at 8 months of age in another study (35). Other reported behavioral deficits include depression-like behavior and either increased (35,37) or decreased (33) anxiety.…”
Section: Mouse Models Of Progranulin Deficiencymentioning
confidence: 92%
“…Recent studies revealed an abnormal accumulation of lipofuscin granules in mice brain regions with ablation of progranulin, accompanied by significantly increased p62 (Bjørkøy et al 2005, Wils et al 2012, suggesting impairment of the autophagylysosomal system in mice brains with ablation of progranulin. Furthermore, autophagy has been closely linked to inflammation in part by regulation of adipokine production.…”
Section: Introductionmentioning
confidence: 99%